Foliar structural differences between glyphosate-resistant and susceptible biotypes of Digitaria insularis (L.) Fedde - Ferreira, Silvio Douglas (2022)
We had, as an objective, characterizing, anatomically, the leaves of two populations of D. insularis (resistant biotype and susceptible biotype), which were collected in cropping areas in Paraná. In order to do this, a trial design in random sets was employed, which were repeated ten times. To obtain the data, it was evaluated the structural and quantitative variables of foliar blades of anatomical parts, which belonged to different leaves in the mature stage that were removed from distinct resistant and susceptible biotypes of D. insularis. The structural variables of the cross-sectional parts evaluated from the foliar blades were: the thickness of the foliar blade in the intercostal region (TBI); thickness of the keel (TK); stomata number (SN) and thickness of cuticle (TC) in the adaxial and abaxial faces. The resistant biotypes of D. insularis differ from the susceptible ones in several structural parameters, among them, there is the foliar blade in the interveinal region that was 7.3 ticker in the resistant biotype, which was also observed in the thickness of the keel, in the percentage of 11.3%, and in the thickness of the cuticle in the adaxial face (TCD), which was 53.8% thicker in the resistant biotype. In this way, we concluded that the anatomical foliar characteristics observed in the resistant biotypes, which differ from the susceptible ones, can be related to the reduction in the absorption and the herbicides translocation speed, constituting, therefore, possible mechanisms of resistance to glyphosate